PEMANFAATAN KULIT BAWANG MERAH (ALLIUM CEPA L.) DAN BAWANG PUTIH (ALLIUM SATIVUM L.) SEBAGAI PESTISIDA NABATI UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN - Gurabha, Habil Al; Jurnal Wicara; Ananda, Azkiya Ayu; M, M. Zaidan Asykar; Rahayu, Sri Puji; Ananda, Febby Marsya; Ainurrofika, Ainurrofika; Aprilia, Ilmi; Muhaimin, Arif; Kurniawati, Ervina; Apriani, Annisa Rizki Nur; Haryanto, Hery (Universitas Mataram, 2025)
Farmers’ dependence on synthetic pesticides has caused negative impacts such as environmental pollution, harmful residues, and health risks. As an alternative, botanical pesticides provide an eco-friendly solution that is simple to prepare and safe to use. This article discusses a community empowerment program in Sembalun Tourism Village through training on producing botanical pesticides made from onion (Allium cepa L.) and garlic (Allium sativum L.) peels-household waste with potential bioactive compounds. The program was conducted in 1 August 2025 through observation, socialization, and demonstration. The process involved grinding onion and garlic peels with water, fermenting for 48 hours, filtering, and applying the extract to local horticultural crops. Field trials showed a reduction in pest eggs and larvae, although effectiveness was still lower compared to synthetic pesticides. The community response was highly positive, with more than 80% of participants attempting independent preparation of botanical pesticides. Main challenges included short shelf life of the extract and variability in raw material quality. Overall, the program successfully raised environmental awareness, reduced organic waste, and encouraged sustainable agricultural practices.